MANAJEMEN STRATEGI PELAYANAN PRIMA PERBANKAN SYARIAH DALAM MENINGKATKAN NASABAH BSI - Carnendi Haryono; Akhmad Aflaha (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
Increasingly, competition between banks is getting tighter. For this reason, of course banks must have a strategy so as not to lose their customers. One method that can be used is in terms of service, so the best service must be continuously sought so that the bank does not lose customers. The aim of the research is to find out what the excellent service strategy is in increasing the number of customers at Bank BSI KC Arjawinangun and also to find out what the obstacles are in the excellent service strategy in increasing the number of customers at Bank BSI KC Arjawinangun. The research method used is field research, with a qualitative approach. The subject of this research is Bank BSI KC Arjawinangun, the object of this research is the excellent service strategy in increasing the number of customers. The data collection techniques used were interview observation and document study. The research results show that (1) The excellent service strategy implemented by Bank BSI KC Arjawinangun is by providing the best service to customers, (2) there is training for Bank BSI KC Arjawinangun employees so that these employees already know how to serve customers well, (3) and apart from that, BSI KC Arjawinangun bank also carries out a strategy of offering products to customers that suit customer needs. The obstacles are: (1) Lack of public understanding about sharia banking which assumes that sharia banks are the same as conventional banks, (2) The presence of other banks that also use excellent service strategies, and (3) Experiencing offline networks and a lack of customer understanding